Contrast-Enhanced Ultrasound in Renal Transplants: Applications and Future Directions - Harvey, C. J.; Sidhu, P. S.; Bachmann Nielsen, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
The role of contrast-enhanced ultrasound (CEUS) in the detection and characterisation of focal liver lesions is well established 1. The renal applications of ultrasound contrast agents (UCAs) have increased and diversified since their introduction 234567 and recent guidelines have underlined their importance in the renal transplantation 4. Ultrasound contrast agents are simple to use and are well tolerated by patients 8. They can be safely used in renal impairment and obstruction unlike computed tomography (CT) and magnetic resonance (MR) agents. The imaging methods operate in real-time, often allowing a diagnosis to be promptly attained without exposure to ionising radiation, the fear of claustrophobia and at a lower cost than CT or MR imaging. Normally, B-mode and Doppler ultrasonography are the modality of choice for imaging the transplant kidney; excellent at assessing graft vascularity, diagnosing obstruction, detecting peri-nephric collections, focal masses and cysts. B-mode and Doppler ultrasonography have limitations in the assessment of the renal transplant microcirculation, cortical perfusion and deciphering focal masses or complex cysts. Before the introduction of UCAs focal lesions would be further characterised by contrast-enhanced CT and magnetic resonance (MR) imaging and there was no reliable non-invasive method of assessing the microcirculation.The application of CEUS in renal transplants highlights its versatility in immediate problem solving, without recourse to other potentially nephrotoxic agents. In addition CEUS can uniquely provide additional information not available from other modalities about the microcirculation. This is elegantly illustrated in the article by Fernandez et al. 9, where renal cortical necrosis is clearly depicted, allows immediate clinical management and adds to the knowledge in this expanding field.It is important to have a clear understanding of the background, current applications and potential for UCAs in the evaluation of the renal transplant to appreciate the value of CEUS in this domain.Microbubbles 1011 consist of a complex gas (e.g perfluorocarbon gas) stabilized by a phospholipid, or polymer shell and are of the size of a red blood cell, small enough to cross capillary beds but are too large to enter the interstitial fluid and therefore serve as pure intravascular agents. Renal ultrasound contrast agent dynamics differ from CT and MR contrast agents; UCAs remain entirely intravascular, are not excreted by the kidneys and therefore have no nephrographic or excretory phase. Following an intravenous bolus of UCAs the cortical phase (90 % of renal perfusion) begins 10 – 15 s after injection and lasts 20 – 40 s followed by a slower medullary phase lasting 45 – 120 s. The whole CEUS examination lasts about 3 min. CEUS allows imaging of vessels down to 100 μm in diameter which is well below the 1 mm resolution limit of conventional Doppler techniques. Therefore, CEUS is excellent at assessing the vascular complications of renal transplants, can exquisitely image the microcirculation and is very sensitive in the detection of infarction (which shows as a defect on all phases of enhancement). The defect on CEUS appears smaller than on the corresponding Doppler study because of this ability to depict flow in the microcirculation. Perfusion defects appear as focal wedge shaped areas of absent, decreased or delayed contrast enhancement compared with the adjacent renal parenchyma 12. As Fernandez et al. 9 confirm cortical necrosis is rendered more conspicuous by CEUS, making this an exquisite tool for bedside assessment of transplant vascularity.Quantitative methods can be applied to the kidney (native or transplant) using low or high acoustic power techniques 13. Since microbubbles are pure blood pool agents their transit through a region of interest can be followed using a low acoustic power technique. A time intensity curve (TIC) can be generated and a number of indices can be derived such as arrival time, time to peak intensity, area under the curve and rate of washout. Alternatively a high energy reperfusion technique can be used to measure perfusion 14. This may play a role in the assessment of transplant perfusion and the early detection of complications. B-mode ultrasound is poor at discriminating between the important causes of early graft dysfunction, especially acute tubular necrosis, rejection, and drug toxicity: these important distinctions still rely on biopsy. Recent work with UCAs has provided hope that functional data from microbubble contrast agent dynamics might produce useful information for their detection and differentiation, thus directing management and possibly avoiding the need for biopsy. Recent studies using microbubbles to measure renal flow in renal transplants have shown promising results in terms of monitoring graft function and directing anti-rejection therapy 1516171819.CEUS can be helpful in the characterisation of focal tumours in the native and transplant kidney, with typical differential hyper or hypo enhancement compared to the adjacent cortex. Cystic or avascular necrotic components can be distinguished from viable tumour as they appear as conspicuous signal voids. However, current CEUS guidelines 4 indicate that there are no specific patterns which reliably differentiate benign from malignant renal tumours. Although tumours are uncommon in renal transplants, cysts are frequently encountered and the superior spatial and temporal resolution of CEUS, real-time imaging allows visualisation of flow within septa, nodules and cyst wall which cannot be imaged on conventional US techniques, contrast-enhanced CT or contrast-enhanced MR 20212223. A CEUS Bosniak classification is likely more sensitive than a CT classification 23 when adapted for ultrasonography 21, and should be more accurate in the evaluation of cystic structures in the superficially located renal transplant. CEUS is usually unnecessary in the diagnosis of renal artery thrombosis or stenosis but can be used in difficult cases. CEUS is also excellent in assessing venous patency in renal transplants in problem cases and also distinguishing bland from tumour thrombus.In conclusion CEUS is a safe and excellent method for assessing the renal transplant vasculature and can be used in the diagnosis of renal infarction, renal arterial/venous thrombosis, as well as the non-invasive quantification of cortical perfusion and the microcirculation. CEUS provides unique functional data in grafts with promising results in terms of monitoring graft function and directing anti-rejection therapy. CEUS may characterise indeterminate renal lesions, complex cysts and focal inflammatory lesions to rival CT and MR imaging. The possibility of visualising and diagnosing acute cortical necrosis adds to the already formidable armamentarium of the physician who uses CEUS in assessing the renal transplant. All of this without any nephrotoxicity!